MODEL PERUBAHAN VOLUME KERIPIK BUAH SELAMA PROSES PENGGORENGAN SECARA VAKUM [Model for Volume Changes in Fruit Chips during Vacuum Frying] - . Jamaluddin; Budi Rahardjo; Pudji Hastuti; . Rochmadi (Jurnal Teknologi dan Industri Pangan, 2011)
Expansion and puffing are specific characteristics of fried products critical for consumer preferences. To obtain expanded and puffed dried products that fit well with consumer acceptance criteria, it is necessary to pay attention to the process conditions which change the raw material characteristics during frying. The important changes include volume and density ratio of the products during frying. Hypothetically, these changes are due to water vaporization and the decrease dry matter in the products. The objective of this research is to develop a mathematical model of volume and density ratio changes for jack fruit during vacuum frying as a function of water and starch content reductions. Samples were vacuum fried at 70–100OC and pressure of 80-90 kPa for 15–60 min. The parameters observed were volume and density as well as water and starch contents of samples before and after vacuum frying. The results showed that the developed model can be used to predict changes in volume and density ratio of jack fruit during vacuum frying.